Mirage or reality?: impulses, obstacles and challenges of the new Government - Cascante, Kattya (Revista Española de Desarrollo y Cooperación, 2023)
This article analyzes the recent Government Administration’s measures for the Spanish policy of international development cooperation, to renew the commitments and the action framework of the 2030 Agenda and the Aid for Development policy.These could just be a mirage in case the resources and a sufficient legal-institutional framework aren’t obtained to face the assumed commitments and upcoming challenges.